A geometry-based design approach and structural behaviour for an asymptotic curtain wall system. (15th July 2022) - Schling, Eike; Wan, Zongshuai
Abstract: This paper presents a novel design approach for doubly curved façade structures, based on isothermal networks on minimal surfaces. It combines theories from differential geometry with knowledge in mechanical behaviour and architectural design. By controlling the curvature of surface and network, and allowing the elastic deformations of elements, a curtain wall system is fabricated from straight steel strips, assembled with repetitive 90-degree joints, and covered with planar quadrilateral or developable panels. The goal of this research is to study the complete workflow from digital design through simulation to the physical construction of a 2.4 × 2.4 m steel structure. The article presents the computational and mathematical method to design minimal surfaces, find the path of asymptotic and principal curvature lines, and create isothermal networks. To analyse elastic stress, two methods are compared using analytical beam theory and a novel flatten-reduction approach for Finite Element (FE) shell elements. The novel approach offers benefits in manufacturing, logistics, prefabrication and erection process. The FE method is used to analyse the bent structure, simulate the kinetic behaviour and evaluate the impact of residual stress, lamella slots, joint reinforcement on the structural performance. The study offers a systematic workflow to accurately design for construction and predict kinetic and static behaviour. It provides evidence of the feasibility of this strategy to create low-cost, resilient, smooth doubly curved façade structures. Graphical abstract: Image 1 Highlights: Design and construction of an innovative asymptotic curtain wall system. A geometry-based design approach allows to control the complexity of fabrication. The kinetic behaviour, and impact of elastic strains on the load-bearing behaviour are simulated. A method for structural analysis of the elastic strains is developed using FEM. The assembly is aided by a self-forming erection process, which is verified experimentally and numerically.